Haunts of violence in the church : a look at the answer that overcomes violence, a Biblical interpretation of peace and violence - Goeringer, Howard (West Conshohocken, Penn. : Infinity, 2005)
A critique of the "just war" doctrine first espoused by Saint Augustine and a recounting of the history of violence in the Christian Church. The author argues that war and violence are both perversions of the true teachings of Jesus Christ.
How and where peace is found -- When and how the church turned to violence -- The bogus "just war" theory of mainline churches -- Understanding violence in the Old Testament -- The misuse of the New Testament to justify war -- The peace church that continues to live in Christ -- Repent, believe the Gospel and be Jesus' peace church -- Rethinking schools for our children.
Keywords: Pacifism -- Religious aspects; Nonviolence -- Religious aspects; Just war doctrine; Peace; War -- Religious aspects -- Christianity; Violence -- Religious aspects